An empirical investigation of the coordinated development of natural resources, financial development and ecological efficiency in China. (March 2020) - Zameer, Hashim; Yasmeen, Humaira; Wang, Rong; Tao, Jing; Malik, Muhammad Nasir
Abstract: The role of financial development, natural resources and ecological efficiency has generated many attractive avenues for scholarly research, but only few studies have evaluated the coupling coordination degree of natural resources, financial development and ecological efficiency in China from regional perspective. Taking a natural and socio-economic dynamics into accounts, this study explores the coupling coordination degree of natural resources, financial development and ecological efficiency using the data of three Chinese regions i.e. Eastern, Central and Western region from 2006 to 2018. We employed entropy weight method and coupling coordination degree evaluation method for data analysis. The findings of the study show that the financial development of the central and western regions was higher than that of the eastern region. Secondly, although the eastern region lacks natural resources, but its resource utilization efficiency is high. In contrast, the central and western regions are rich in resources, but the utilization efficiency is low. It shows that the regions with relatively backward economic development are over-reliant on natural resources. Thirdly, the ecological efficiency in the central region is lower than that in the eastern region, but it is larger than that in the western region. Finally, the study concludes with some policy implications. Highlights: Entropy weight method and coupling coordination method used. Financial development of the eastern region is lower than other regions. Resources utilization efficiency of the eastern region is high compared with other regions. Ecological efficiency in the central region is lower than other regions.